Análisis del agua de consumo humano para la determinación de un sistema de tratamiento, en la parroquia El Triunfo, cantón y provincia de Pastaza, periodo 2014 - Calunia Rojas, Alexandra Herminia (2015)
This research was conducted in order to find the most optimal way to provide safe drinking water to the population and this is the implementation of a water treatment system by gravity with aeration, filtration and chlorination, in the parish El Triunfo Pastaza canton and province. Making a diagnosis environmental water sampling water and then a physical analysis - chemical and microbiological that is done in specialized laboratories. The system of drinking water by gravity, is a set of efficient processes in treating groundwater, which are in a simple and easy plant to operate in rural aqueducts, is designed to treat of flow 3 l / s for type water groundwater is easily portable compact type of transported or move from place, adapts to any environment; the manufacturing materials are fiberglass, steel and polyethylene….